Pengaruh Pemberian Yoghurt Susu Kambing Dengan Bakteri Asam Laktat Terhadap Kadar Fraksi Lipid Tikus Putih Hiperlipidemia - Ratih Hardisari; Saptono Putro (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
Hyperlipidemic or elevated cholesterol levels in the bloodstream is a risk factor for coronary heart disease, which is the leading cause of death in the world. Yoghurt is fermented milk containing lactic acid bacteria that can lower cholesterol and trigliserida level. Goat milk is milk that has advantages easily digested because it has a smaller globule size and has a therapeutic value and is hypoallergenic, so safe to be consumed by everyone. To determine the effect of giving goat milk yoghurt with Lactobacillus acidophilus and Bifidobacterium to lipid fraction levels in hyperlipidemic white rats. The pure research experience using Pre-test - Post-Test With Control Group Design with 30 samples induced-hyperlipidemic Sprague Dawley rats consisting of 5 treatment groups, include negative control group, positive control group, simvastatin group (dose 0.18 mg/200 gram BB), treatment 1 group (dose 2.7 ml / 200 gram BB) and treatment 2 group (dose 5.4 ml/200 gram BB). The data obtained were treatment descriptively and statistically presented in the form of tables and graphs. Goat milk yoghurt with Lactobacillus acidophilus and Bifidobacterium bacteria with a dose of 2.7 ml / 200 gram BB/ day; doses of 5.4 ml/200 gram BB/day; and simvastatin drugs may lower lipid fraction levels with a median percentage of successively showing Cholesterol results 41,24%, 53,65% and 47,92%, Triglycerides 59,75%, 56,39% and 60,52%, HDL yields 56.67%, 65.70% and 69.79%, LDL 66.46%, 54.24% and 72.02%. The results of data analysis in statistics using One Way ANOVA showed that there was a difference of lipid fraction level in each treatment group significantly (p<0.05). There is an effect of giving goat milk yoghurt with Lactobacillus acidophilus and Bifidobacterium on lipid fraction levels in white rats.